Online Gambling Phenomenon: Law & Society - Delfi Aurelia Kuasa; Febri Jaya (Universitas Widya Gama Malang, 2022)
The gambling phenomenon has been happening for a long time. Development of science and technology causes new ways to commit crimes. One of the crimes that occur is online gambling. This can happen due to facilities and media that make it easier for people to access sites and applications that have elements of gambling. To eradicate this action, a provision that strictly prohibits the act with consequences for the violators is needed. The online gambling act not only violates Indonesia's laws, but it also violates the values and norms embraced by the community. Although it has been prohibited by Indonesian law, online gambling cases are still widely found in the community. To find out why, the sociology of law is needed to find out the relationship between law and society. Viewed from the sociology of law’s point of view, especially the effectiveness of the law according to Soerjono Soekanto, the law on conventional and online gambling are still not fully effective. This is because there are still inconsistencies between applicable laws and social values, lack of legal certainty, lack of supporting facilities for law enforcement, lack of awareness and knowledge of the law, and lack of community participation in law enforcement actions. The research method is non-doctrinal or empirical legal research method which is carried out with statute approach and sociological approach. This research aims to determine the sociology of law’s perspective on online gambling that occurs in society.